Program Pembuatan Tempat Sampah dalam Meningkatkan Kualitas Pendidikan di SMK Negeri Balanipa - Husain Husain; Nurfadillah R; Nurhayati N; Ramli M; Agustini S (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2024)
The results of the KKN team's observations at Balanipa Vocational School show that the creation of a clean and healthy environment that supports the learning process has not been fully fulfilled. As an effort by the KKN TEAM to encourage the creation of a clean and healthy environment for quality education, several appropriate work programs have been carried out. One step to make this happen is by completing infrastructure that supports the creation of a clean and healthy environment, such as providing rubbish bins. This is a solution because the results of observations show that the number of existing rubbish bins does not match the number of school residents such as students, teachers, staff and parents who come to visit to throw away the rubbish. As an effort to do this, the KKN team first identified the number and location of trash bins needed at Balanipa Vocational School. Next, collaboration was carried out with the KKN team and the school community (students and teachers) to collect basic materials in the form of bamboo to make trash cans. About 12 trash bins were produced which were then placed in every corner of the building and in front of every room. The results of further observations show that a clean and healthy environment has been created thanks to the presence of the new trash can. This is proven by the trash cans being almost full every day.